DIFERENSIASI PEMBELAJARAN IPAS PADA KURIKULUM MERDEKA MELALUI ASESMEN DIAGNOSTIK DI SEKOLAH DASAR - Shella Nerisa Arviana; Rizki Navila; Devinta Cahyani; Muhammad Immadudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe and analyze the implementation of differentiated Social Sciences and Science (IPAS) learning through initial diagnostic assessments under the Independent Curriculum framework at SDN Magetan 2. This field research utilizes a qualitative descriptive approach with a field study design, gathering data through direct classroom observation, lesson plan analysis, and structured interviews with grade teachers. The evaluation utilized 15 comprehensive observation indicators covering document readiness, technological integration, local wisdom contextualization, assessment methods, and differentiation strategies. The results demonstrate that teachers at SDN Magetan 2 have designed teaching instruments systematically by modifying the government template to suit classroom characteristics based on diagnostic profiles (auditory, visual, and kinesthetic). Active student collaboration is fostered through Project-Based Learning (PjBL) integrated with deep learning models, supported by multimedia tools and local culture integration, such as the Sarangan tradition. Assessments are carried out comprehensively across cognitive, affective, and psychomotor domains using jobpartitioning strategies during group work. Differentiated instruction is successfully realized through peer tutoring for advanced learners and direct oral-guiding for slower learners. In conclusion, differentiated learning based on diagnostic assessments shapes meaningful, inclusive, and student-centered primary education.